Peningkatan Aktivitas dan Hasil Belajar Pendidikan Jasmani dan Kesehatan melalui Metode Course Reivew Horay pada Siswa kelas VI SD Negeri 2 Natar Lampung Selatan Tahun Pelajaran 2019/2020 - Subroto Subroto (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2022)
The purpose of this study is to increase activities and learning outcomes of Physical Education through the course review method for Class VI students of SD Negeri 2 Natar, Natar District, South Lampung, for the 2019/2020 academic year. CAR research method in 3 learning cycles, each consisting of planning, action, observation, reflection. This research was conducted at SD Negeri 2 Natar, South Lampung, in the odd semester of the 2019/2020 academic year. The research data was taken from observing the activities and learning outcomes of students and colleagues. Cycle I learning outcomes 61%, learning activities 62%, cycle II learning outcomes increased to 73% and Activities 81%, cycle III learning outcomes increased to 82%, learning activities 85%. Conclusion The use of the Course Review Horay (CRH) model can improve activities and learning outcomes of Physical Education in Class VI students of SD Negeri 2 Natar South Lampung 2019/2020.